Case Report: Pink Urine Syndrome Following Exposure to Propofol: A Rare, Impressive but Benign Complication - Zhang, Fangwei; Zhu, Xing; Zhang, Hongbo; Xu, Lin; Wu, Weiguo; Hu, Xuelei; Zhou, Haipeng; Wei, Penghui; Li, Jianjun (Frontiers in Pharmacology, 2021)
Drug-induced changes in urine color induced by drugs may have clinical significance. Pink urine syndrome (PUS), which has been associated with urinary uric acid (UA) disorders, is most frequently reported in patients with morbid obesity undergoing gastric bypass surgery and/or from propofol anesthesia use in those who potentially have preexisting UA metabolism disorders. However, PUS has rarely occurred following exposure to propofol in non-obese patients, and literature on long-term follow-up after PUS is scarce. We report a case of PUS induced by propofol in a previously healthy non-obese woman after undergoing thoracoscopic wedge resection of pulmonary nodules under general anesthesia using propofol. The patient suddenly developed pink urine 4 hours after surgery. A pink sediment rapidly precipitated at the bottom of the test tube following centrifugation of the urine. Amorphous, colorless UA-like crystals were identified under a polarizing microscope. The diagnosis of PUS was confirmed by examining the urinary UA concentration. The patient recovered and as followed-up for 1 month, during which she did not experience any urinary complications. To our knowledge, this is the first report to describe in detail a case of PUS caused by propofol in a non-obese patient with follow-up. PUS is usually benign and can resolve by rapidly on administering lactated Ringer’s solution; however, the potential risk of urinary complications, particularly UA lithiasis, should be fully realized.